Relationship between psychological distress, quality of life and resilience among medical and non-medical students - Asma Noreen; Nazia Iqbal; Bushra Hassan; Syeda Ayat-e-Zainab Ali (Journal of the Pakistan Medical Association, 2021)
Objective: Medical students are more vulnerable to greater psychological distress and lower quality of life in comparison to non-medical students. However, the resilience among such students can enable them to deal with psychological distress and thus has positive effect on quality of life. This study aimed to identify the associations between psychological distress, resilience and quality of life among medical and non-medical students Methods: A sample of (N=300) Male medical students (n=75) and Female medical students (n=75) Male non-medical students (n=75) and Female non-medical students (n=75) taken from different medical and non-medical colleges or Universities of Rawalpindi and Islamabad. Results: Findings revealed that psychological resilience was a positive predictor of quality of life (b =.30***) whereas psychological distress served as a negative predictor of quality of life (b=-.54***). Medical students were significantly higher on psychological distress (M= 26.81, SD= 7.44, p=.001), whereas non-medical students were found higher on quality of life (M= 91.71, SD = 10.51, p=.001) and resilience (M= 20.52, SD = 3.35, p=.001). Interestingly female students were found higher on Quality of Life (M=89.38, SD=16.28) and male students were found higher on Psychological Distress (M=25.36, SD=6.02, p=.002). Furthermore, male medical and female students were higher on psychological distress and lower on resilience and quality of life. Conclusion: This study calls for implications to develop intervention strategies to deal psychological distress and one such strategy is to promote resilience to improve quality of life among students in general and among medical students in particular. Continuous...